Study of Relationship Between Platelet Parameters and Hyperlipidemia - Gautam, Dipti; Khadgi, Rohit (Nepalese Medical Journal, 2022)
Introduction: Hyperlipidemia is emerging as a major risk factor for developing cardiovascular diseases like atherosclerosis and coronary heart disease. Hyperlipidemia in turn results in platelet activation and thrombotic events. Platelets have been shown to have a role in the thrombus consequences of atheromatous damage in hyperlipidemic individuals by initiating and propagating atherosclerotic plaques. Platelet activity can be evaluated with platelet indices, including platelet distribution width and plateletcrit. Materials and Methods: This was a prospective study carried out over a period of one month in the Department of Pathology, Patan hospital. A total of 223 subjects with hyperlipidemia and 35 controls with normal lipid profiles and PDW were included. Statistical analysis was done using Pearson’s correlation test and data were expressed as mean ±SD for each parameter. A p-value of < 0.05 was considered to be significant. Results: Maximum number of patients was in 41-60 years of age (42.6%). The male-to-female ratio was 1: 1.1 with 47% males and 53% females. The mean total cholesterol, mean LDL-C, and mean HDL-C of the study group were 230.4±26.7, 150.3±28.4, and 40.9±15.2 respectively. The mean platelet count and PDW were 288.9±230.5 and 14.1±3.3 respectively. There was a significant correlation between PDW with total cholesterol and LDL-C in a study group with a p-value of <0.001. Conclusions: The present study indicates that PDWs are significantly higher in patients with hyperlipidemia. These indices are available without any additional cost to clinicians, pathologists, and patients and can be used to assess the risk associated with hyperlipidemia.